Ответы и объяснения

2013-09-18T15:30:34+00:00
1) х+5у=7 * (-3)                              2) 3х+2у=-5
   3х+2у=-5                                        3х+2*2=-5
                                                         3х+4=-5
                                                         х=-3
                                                      
                                                        3) {x=-3
                                                            {y=2
 -3х-15у=-21
+
  3х+2у=-5
       -13у=-26
         у=2